Expansion With IL-15 Increases Cytotoxicity of Vγ9Vδ2 T Cells and Is Associated With Higher Levels of Cytotoxic Molecules and T-bet - Aehnlich, Pia; Carnaz Simões, Ana Micaela; Skadborg, Signe Koggersbøl; Holmen Olofsson, Gitte; thor Straten, Per (Frontiers in Immunology, 2020)
Cancer immunotherapy has shown great advances during recent years, but it has yet to reach its full potential in all cancer types. Adoptive cell therapy (ACT) is now an approved treatment option for certain hematological cancers and has also shown success for some solid cancers. Still, benefit and eligibility do not extend to all patients. ACT with Vγ9Vδ2 T cells is a promising approach to overcome this hurdle. In this study, we aimed to explore the effect of different cytokine conditions on the expansion of Vγ9Vδ2 T cells in vitro. We could show that Vγ9Vδ2 T cell expansion is feasible with two different cytokine conditions: (a) 1,000 U/ml interleukin (IL)-2 and (b) 100 U/ml IL-2 + 100 U/ml IL-15. We did not observe differences in expansion rate or Vγ9Vδ2 T cell purity between the conditions; however, IL-2/IL-15-expanded Vγ9Vδ2 T cells displayed enhanced cytotoxicity against tumor cells, also in hypoxia. While this increase in killing capacity was not reflected in natural killer (NK) cell marker or activation marker expression, we demonstrated that IL-2/IL-15-expanded Vγ9Vδ2 T cells were characterized by an increased expression of perforin, granzyme B, and granulysin compared to IL-2-expanded cells. These cytotoxic molecules were not only increased in a resting state, but also released to a greater extent upon target recognition. In contrast, CD107a and cytokine expression did not differ between expansion conditions. However, IL-2/IL-15-expanded Vγ9Vδ2 T cells showed higher levels of transcription factor T-bet expression, which could indicate that T-bet and cytotoxic molecule levels confer the increased cytotoxicity. These results advocate the inclusion of IL-15 into ex vivo Vγ9Vδ2 T cell expansion protocols in future clinical studies.